LED FLUORESCENCE MICROSCOPY: LEADS THE FUTURE OF RAPID AND EFFECTIVE PULMONARY TUBERCULOSIS DIAGNOSIS - VISHNU PRASAD SHENOY,; SEEMA SHETTY,; CHAITANYA TELLAPRAGADA,; CHIRANJAY MUKHOPADHYAY, (International Journal of Pharma and Bio Sciences, 2014)
Early diagnosis and appropriate treatment play an important role in combating the mortality and morbidity caused by Tuberculosis and a rapid, reliable microscopy that can detect acid fast bacilli can be a very useful diagnostic modality. We have evaluated the performance of Light Emitting Diode Fluorescence Microscopy as an alternative to the existing conventional methods in the diagnosis of Pulmonary Tuberculosis.total of 181 sputum samples received at the Microbiology laboratory of Kasturba Hospital, Manipal were examined by three different microbiologists using Ziehl-Neelsen’s (ZN), Fluorescence microscopy (FM) and Light Emitting Diode fluorescence microscopy (LED). Results were independently tabulated by all the three examiners for comparison of the efficacies of FM and LED in detecting the tubercle bacilli. Of the 181 samples, 25 (13.8%) were positive by all the three microscopic examinations. We did not observe any better sensitivity of the FM or the LED compared with the conventional ZN method. The measure of agreement between FM and LED was excellent and statistically significant (Kappa= 0.817; P value <0.01). LED is a promising reliable alternative that can replace both conventional ZN and FM. As it shortens the diagnostic process and being cost effective should be considered by all TB diagnostic laboratories for increased case finding and rapid diagnosis of Pulmonary Tuberculosis.